O papel da funcionalização de MOFs (Metal-Organic Frameworks) para a melhoria da eficiência e seletividade de adsorção de metais pesados - Theodoroviez, Lucas Bitencourt [UNESP] (Universidade Estadual Paulista (Unesp), 2021)
Heavy metals are one of the main contaminants of water and soil in Brazil, thus generating a great impact on the macro ecological and economic scenario. Currently, the forms of metal extraction include equipment that complement high energy usage and maintenance costs. In this scenario, there is an alternative possibility of using porous matrices for the adsorption of these elements, which can lead to a decrease in process costs, also guaranteeing an emergency way to contain these toxic elements. From this perspective, this work aims to synthesize, functionalize and investigate the potential application of a new class of porous inorganic materials in the adsorption of toxic metal ions. These are known as MOFs (Metal-Organic Frameworks). These materials can present high stability to changes in pH and temperature, in addition to having high crystallinity and specific high area (in some systems they can reach values of up to 10,000 m2 .g-1 ). These materials are also passive to chemical functionalization, that is, an incorporation of groups in their pores or on the surface, and can therefore improve some property. Within this context, the starting material chosen was MOF808, synthesized from the covalent interaction between zirconium(IV) ions and the 1,3,5-benzene tricarboxylic acid (BTC) ligand, mainly for its excellent chemical stability. The work continued in order to functionalize this porous matrix, using the functionalizing agents EDTA and L-cysteine, giving rise to the formation of the materials MOF-808-EDTA and MOF-808-Cys, respectively. Because they are highly reactive with heavy metals, these functional groups lead to the successful formation of porous matrices with great affinity for the ions that are the object of this study: the Hg(II), Pb(II) and Cd(II) ions. The removal of these ions from aqueous solutions by MOFs have in some cases reached values as high as 99% and for the material MOF808-Cys, a selectivity for the mercury (II) ion. The results obtained in this work revealed an efficiency of materials based on functionalized MOFs for adsorption of heavy metals and the great potential for use in bioremediation.

Os metais pesados são um dos principais contaminantes de água e solo no Brasil, gerando, assim, grande impacto no cenário macro ecológico e econômico. Atualmente, as formas de extração desses metais incluem equipamentos complexos que necessitam de grande utilização de energia e gastos com manutenção. Nesse cenário, há a possibilidade alternativa de usar matrizes porosas para a adsorção desses elementos, o que pode levar à diminuição dos custos do processo, garantindo, também, uma maneira emergencial de contenção desses resíduos tóxicos. Sob essa perspectiva, esse trabalho pretende sintetizar, funcionalizar e investigar a potencialidade de aplicação de uma nova classe de materiais porosos inorgânicos na adsorção de íons metálicos tóxicos. Trata-se das Redes Metalorgânicas ou MOFs (Metal-Organic Frameworks). Esses materiais podem apresentar alta estabilidade a mudanças de pH e temperatura, além de possuírem alta cristalinidade e elevada área específica (podendo em alguns sistemas alcançar valores de até 10.000 m^2/g). Esses materiais são, ainda, passivos a funcionalização química, ou seja, a incorporação de grupos funcionais em seus poros ou na sua superfície, podendo, portanto, melhorar substancialmente alguma propriedade. Dentro desse contexto, o material de partida escolhido foi a MOF-808, construída a partir da interação covalente entre íons zircônio(IV) e o ligante ácido 1,3,5-benzenotricarboxílico (BTC), principalmente por sua excelente estabilidade química. O trabalho prosseguiu no sentido de funcionalizar essa matriz porosa, utilizando os agentes de funcionalização EDTA e L-cisteína, dando origem à formação dos materiais MOF-808-EDTA e MOF808-Cys, respectivamente. Por terem alta afinidade com metais pesados, esses grupos funcionalizantes conduziram à formação com sucesso de matrizes porosas com grande potencialidade de captura de pelos íons objetos desse estudo: os íons Hg(II), Pb(II) e Cd(II). A remoção desses íons de soluções aquosas pelas MOFs alcançou em alguns casos valores tão altos quanto 99% e para o material MOF-808-Cys, uma significativa seletividade para o íon mercúrio(II). Os resultados obtidos nesse trabalho revelaram a eficiência de materiais baseados em MOFs funcionalizadas para adsorção de metais pesados e a grande potencialidade para uso em biorremediação.
The role of the functionalization of MOFs (Metal-Organic Frameworks) to improve the efficiency and selectivity of heavy metals adsorption
Keywords: MOFs; Metais pesados; Materiais porosos; Meio-Ambiente; Funcionalização